تقييم حدة الجفاف في اللاذقية والرقة باستخدام مؤشر الكشف عن الجفاف ((RDI - جـلب, أدهـم; شيخو, طاهر; ديبه, راميا (Latakia University Journal -Biological Sciences Series, 2019)
تعد ظاهرة الجفاف من المخاطر الطبيعية التي تهدد حياة البشر والنظم البيئية المختلفة في مناطق واسعة من العالم بما فيها القطر العربي السوري. أظهرت نتائج تقييم الجفاف باستخدام مؤشر الـ RDI خلال المدة (1975-2006) بأن العام الهيدرولوجي الأشد جفافًا (جفاف متطرف) في محطتي اللاذقية والرقة هو 2000-2001 و 1983-1984 على التوالي، وقد بلغت قيم مؤشر الجفاف لكل منهما -2.7) و -2.2). وتردد الجفاف المتطرف السنوي مرة واحدة في اللاذقية ومرتين في الرقة، بينما تكرر الجفاف الشديد ثلاث مرات في الرقة ولم يقع في اللاذقية؛ وعلى المستوى الفصلي وقع الجفاف المتطرف مرتين في ربيع اللاذقية ومرة واحدة في خريفها، في حين وقع مرة واحدة في شتاء الرقة ومرتين في خريفها؛ وأما الجفاف الشديد فقد تكرر مرتين في شتاء وربيع كل من اللاذقية والرقة ومرة واحدة في خريف اللاذقية؛ وعلى المستوى الشهري كان شهر أيار هو الأكثر تعرضاً للجفاف المتطرف في محطتي الرقة واللاذقية بنسبة 40,6% و 25% على التوالي، يليه شهر تشرين الأول بنسبة 28,1% في الرقة وشهر تشرين الثاني بنسبة 6,3% في اللاذقية. The drought phenomenon is one of the natural hazards that threaten human life and the various ecosystems in large areas of the world, including the Syrian Arab Republic. Results using the RDI drought index during the period (1975-2006), indicated that the driest hydrological year (extreme drought) in Lattakia was (2000-2001) and in Al-Raqah was (1983-1984), with RDI values of (-2.7, -2.2). The frequency of the annual extreme drought was twice in Al-Raqah and once in Lattakia, while the severe drought occurred three times in Al-Raqah and did not occur in Lattakia. On a seasonal scale, the occurrence of the extreme drought took place once in Winter of Al-Raqah and twice in spring of Lattakia, and twice in Winter and Spring in both Lattakia and Al-Raqah. However, the frequency of severe drought took place twice in Winter and spring in both Lattakia and al-Raqah and once in Autumn of Lattakia. On a monthly basis, May was the most vulnerable to extreme drought in both Lattakia and Al-Raqah with a percentage of 40.6% and 25%, respectively, followed by October with 28.1% in Al-Raqah, and November with 6.3% in Lattakia.